2004
DOI: 10.1081/pfc-120030245
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation Kinetics and Bioconcentration Factor of Chlorinated Pesticides in Tissues ofPuntius ticto(Ham.)

Abstract: Bioaccumulation kinetics and bioconcentration factor (BCF) of chlorinated pesticides like Aldrin, Dieldrin, Benzene hexachloride (BHC), and Dichlorodiphenyl-dichloro-ethane (DDT) in fish tissues of Puntius ticto was studied in detail in a continuous fed system. The bioconcentration process is summarized by using a first order uptake model and the steady-state BCF is calculated based on the 30 days exposure. Rate of bioaccumulation of DDT was maximum of 4.6432 microg g(-1) wet weight per day in liver tissue whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…It is assumed to result from the protective effect of garlic. Barathinivas et al (2022) Similar results have been reported for Cyprinus carpio and Puntius ticto (Satyanarayan et al, 2004), Cyprinus carpio (Saravanan et al, 2017), Oreochromis mossambicus (Ghayyur et al, 2019) and Oreochromis niloticus (Dawood et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…It is assumed to result from the protective effect of garlic. Barathinivas et al (2022) Similar results have been reported for Cyprinus carpio and Puntius ticto (Satyanarayan et al, 2004), Cyprinus carpio (Saravanan et al, 2017), Oreochromis mossambicus (Ghayyur et al, 2019) and Oreochromis niloticus (Dawood et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
“…The study on naphthalene showed formation of lesions and hyperplasty occlusions in gills of Trachinotus carolinus [21] . Also, epithelial lifting, hyperplasia and hypertrophy of respiratory epithelium, lamellar fusion and aneurysms in the gills have been reported in Neotropical fish [22] .…”
Section: Livermentioning
confidence: 97%
“…Other papers report on bioconcentration tests according to OECD TG 305 [1] or U.S. EPA OPPTS 850.1730 [10] without lipid determination being carried out (e.g., [29][30][31][32]). The outcome of the literature review with respect to guideline studies and lipid determination methods was thus not satisfactory due to a shortage of data.…”
Section: Lipid Determination In Bioaccumulation Studiesmentioning
confidence: 99%
“…Variability in muscle concentrations between fish species decreased when concentrations were normalized to lipid content. Several studies describe the residue distribution over different organs (e.g., [31,45,[47][48][49][50][51][52][53]). However, bioconcentration studies according to OECD 305 [1] are performed to obtain BCF values which -per definitionem -refer to the whole fish, and differences in residue distribution over different organs are thus not essential.…”
Section: Differences In Residue Distribution Over Different Organs Anmentioning
confidence: 99%